A new autofocus based on sub-aperture approach - Koo, V. C.; Chan, Y. K.; Chuah, H. T. (Taylor & Francis Group, 2005)
High resolution Synthetic Aperture Radar (SAR) requires the motion of radar platform to be known accurately for precise phase error detection. In SAR processing, autofocus technique is commonly used to estimate the phase errors from the radar data. This paper highlights a novel autofocus algorithm based on subaperture approach, called the Non-overlapping Sub-aperture Autofocus (NSA). As compared to existing autofocus algorithms, the NSA is a computational efficient algorithm that allows the use of dedicated processing unit for real-time implementation. The working principles of the NSA algorithm and its simulation results are outlined in this pape